Biodiesel Production from Mustard Emulsion by a Combined Destabilization/Adsorption Process. (7th July 2015) - Tabtabaei, Solmaz; Boocock, David G. B.; Diosady, Levente L.
Abstract: Tetrahydrofuran, added to the oil‐in‐water emulsions formed by the aqueous processing of yellow mustard flour, produced oil/water/THF miscellas containing 1–2 % water. The high water content prevented the direct conversion of the system to fatty acid methyl esters (FAME) through a single‐phase base‐catalyzed transmethylation process. Dehydration of these miscellas by adsorption on 4A molecular sieves at room temperature using either batch or continuous fixed‐bed systems successfully reduced the water content to the quality standards needed for biodiesel feedstock (0.3 %). Equilibrium adsorption studies for the uptake of water from oil/THF/water miscella phases at room temperature allowed quantitative comparison of the water adsorption capacity based on the oil and THF concentrations of the miscellas. Batch contact was used to investigate the dominant parameters affecting the uptake of water including miscella composition, adsorbent dose and contact time. The adsorption of the water was strongly dependent on adsorbent dose and miscella oil concentrations. The regeneration of molecular sieves by heating under nitrogen at reduced pressure for 6 h at 275 °C resulted in incomplete desorption of miscella components. The adsorption breakthrough curves in terms of flow rates, initial water and oil miscella concentrations were determined. The dehydrated miscella phases were reacted with methanol in a single‐phase base‐catalyzed transmethylation process with high yields (99.3 wt%) to FAME. The resulting FAME met the ASTM international standard in terms of total glycerol content and acid number.